2021
DOI: 10.1029/2021wr030442
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Mineral Reactions in a Translated Single Realistic Fracture: Consequences for Contaminant Uptake by Matrix Diffusion

Abstract: Open fractures are primary conduits for groundwater flow and thus constitute preferential transport pathways for dissolved contaminants. Fracture internal variability, caused, for example, by shearing, leads to significant variability in the in-plane groundwater velocity field (Egert et al., 2021;Zou et al., 2017), which in turn affects mass exchange processes with the stagnant water in the bordering porous rock matrix . Fracture filling minerals, that might have precipitated during past hydrothermal events, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Mineral dissolution occurring during reactive fluid flow in fractures produces distinct dissolution patterns, significantly affecting the permeability and the hydrodynamic behavior of the large-scale fractured rock. Understanding the dissolution dynamics is of particular interest in many geophysical processes, including the cavity enlargement, genesis of karst systems, groundwater contaminant migration, , geological CO 2 storage and leakage, acid injection for stimulating petroleum wells, and dam stability in soluble rocks. The fracture dissolution without buoyancy-driven convection induced by density difference has been extensively studied in previous works. In these circumstances, the fracture dissolution processes are mainly controlled by the interplay among the forced convection of fluid, the diffusion of solute, and the kinetics of reactions. Note that the forced convection of fluid refers to externally imposed flow.…”
Section: Introductionmentioning
confidence: 99%
“…Mineral dissolution occurring during reactive fluid flow in fractures produces distinct dissolution patterns, significantly affecting the permeability and the hydrodynamic behavior of the large-scale fractured rock. Understanding the dissolution dynamics is of particular interest in many geophysical processes, including the cavity enlargement, genesis of karst systems, groundwater contaminant migration, , geological CO 2 storage and leakage, acid injection for stimulating petroleum wells, and dam stability in soluble rocks. The fracture dissolution without buoyancy-driven convection induced by density difference has been extensively studied in previous works. In these circumstances, the fracture dissolution processes are mainly controlled by the interplay among the forced convection of fluid, the diffusion of solute, and the kinetics of reactions. Note that the forced convection of fluid refers to externally imposed flow.…”
Section: Introductionmentioning
confidence: 99%
“…These models mainly focus on the topographic impact on dissolution processes by considering lateral flows (Lebedeva & Brantley, 2017; Myagkiy et al., 2019). Some occasionally study the occurrence of a single fracture on the weathering patterns (Deng & Spycher, 2019; Myagkiy et al., 2019; Trinchero et al., 2021; Zhang et al., 2022). Yet, these models remain rare and do not address the issues of fluid mixing and flow channelization driven by complex discrete fracture network (DFN) geometries because of the challenges of explicitly modeling fracture‐matrix interactions (Berre et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A review listing several observations of flow channeling effects can be found in Tsang and Neretnieks (1998). This channeling behavior is dependent on external drivers such as mechanical stress (Zou et al., 2020) or water‐mineral reactions (Trinchero et al., 2021).…”
Section: Introductionmentioning
confidence: 99%